Coherent Combining of Broadband Radiation Using Multicore Fibers with Square Array of Coupled Cores - Andrianov, Alexey; Kalinin, Nikolay; Anashkina, Elena; Balakin, Alexey; Skobelev, Sergey; Leuchs, Gerd; Litvak, Alexander (2022 Conference on Lasers and Electro-Optics, CLEO 2022 - Proceedings, 2022)
We demonstrate stable propagation of the out-of-phase supermode in a multicore fiber and efficient coherent combination the output radiation in a setup without lenslet array scalable to high power levels applicable to fiber amplifiers.
CRIS-Team Scopus Importer:2023-04-20